Critical analysis of graft loss and death in kidney transplant recipients treated with mTOR inhibitors - Andrade, Luis Gustavo Modelli De; Tedesco-silva, Helio (Sociedade Brasileira de Nefrologia, 2017)
Abstract Registry studies and systematic reviews have shown higher risk for mortality and graft loss in patients in use of mTOR inhibitors (mTORi) compared to calcineurin-based (CNI) immunosuppressive regimens. The majority of these studies pooled data from early trials using different strategies such as de novo combination of the high dose mTOR inhibitors with standard dose of CNI or high dose mTORi combined with mycophenolate. The large heterogeneity of these initial exploratory studies, many of them no longer in use, turns difficult any comparison with a well-defined standard of care regimen. The new strategies using concentration controlled reduced exposure of mTORi and CNI or early conversion from CNI to mTORi use have shown comparable patient and graft survival. Nevertheless, considering the central role of mTOR in health and disease states, more research is necessary to mitigate the adverse events and to explore further the potential beneficial effects of mTOR inhibitors.

Resumo Estudos de registro e revisões sistemáticas mostraram um aumento de mortalidade e perda do enxerto nos pacientes em uso dos inibidores da mTOR (imTOR) em comparação a regimes baseados nos inibidores de calcineurina (iCN). A maioria destes estudos reuniu dados de ensaios clínicos iniciais utilizando diferentes estratégias, tais como a combinação de novo de altas doses de imTOR com doses padrão de iCN ou altas doses de imTOR combinado com micofenolato. A grande heterogeneidade destes estudos exploratórios iniciais, muitos deles não mais em uso, tornam difícil qualquer comparação. As novas estratégias que utilizam a concentração controlada e reduziram a exposição tanto de imTOR quando de iCN mostraram sobrevida do paciente e enxerto comparáveis. No entanto, considerando o papel central dos imTOR nos estados de saúde e doença, é necessária mais investigação para mitigar os eventos adversos e explorar melhor seus potenciais efeitos benéficos.
Análise crítica da perda do enxerto e óbito em receptores de transplante renal tratados com inibidores da mTOR
Keywords: mortality; kidney transplantation; serine-threonine kinases; sirolimus; mortalidade; serina-treonina quinases TOR; sirolimo; transplante de rim